75 anni dopo: Giuseppe Cappi tra i Padri e le Madri costituenti - Pezzini, Barbara (Il diritto ecclesiastico, 2024)
75 years later : Giuseppe Cappi among the Founding Fathers, and Mothers · 75 years after the Constitutional Assembly, the paper proposes a reconstruction of Cappi’s role in that Assembly, moving from previous celebrations which bring to light his individual prestige and the relevance of his speeches during the constitutional debate : among the most significant issues, those relating to jurisdiction, to the Constitutional Court, and to the value of the proportional electoral system. The paper also addresses some resistance shown by Cappi towards gender issues, in particular in the debates on women’s access to the judiciary and on relationships between spouses : son of his time, like a good part of his generation Cappi could not fully understand the prodigious novelty of the very first representative assembly fully participated by women, as voters and as elected representatives.